Emma [compact disc, unabridged] - Austen, Jane, 1775-1817 (Cherry Hill Pub., 2013)
Emma Woodhouse is a lively, intellectual 21-year-old girl who lives with her wealthy father. Despite her intelligence, Emma has little to do and is often quite weary of her empty everyday life. Having few companions of her own age, Emma often entertains herself by attempting to make matches between those around her. She jumps at the chance to help a destitute girl of unknown parentage, Harriet Smith, on her quest to secure the local vicar, Mr. Elton, as a potential suitor.